Interactive eLearning System (IELS) for learning and teaching of ICT course in higher secondary level in Bangladesh / Abu Sayed Md ... [et al.] - Md, Abu Sayed; Hoque, Latiful; Md, Golam; Bashir, Muradul (UiTM Press, 2018)
Introducing ICT course at higher secondary level has created new challenges for computer education in Bangladesh. The challenges are: the crisis of experienced teaching staffs, insufficient laboratory facilities, Internet accessibility and appropriate course materials. So it has become very difficult to provide proper ICT education at higher secondary level. If the ICT education cannot be achieved in these levels, it will have a negative impact to the study of Computer Science and Engineering (CSE) at tertiary level as well. Problem Based e-Learning (PBeL) is the integration of eLearning with Problem-Based Learning, a new paradigm of learning of programming languages and ICT education. In this paper, we have presented an Interactive eLearning System (IeLS) based on Problem- Based eLearning (PBeL) for learning and teaching of the ICT course. The system has been implemented as per syllabus of National Curriculum and Textbook Board of Bangladesh. There are two types of contents in the course: textual and programming. Students can learn the textual contents of the course interactively and measure the learning outcome by self evaluation. The learning and evaluation process is continued iteratively until the learner is satisfied. The programming contents of the course are HTML, C programming and Database Management System. We have implemented the programming contents as per PBeL model. In the PBeL model, the main component is the problem-bank that has been designed in a hierarchical fashion such that the content coverage problem of traditional PBL is removed. So transition from traditional to PBL is easy. The system has been used by the students and teachers of different colleges in higher secondary level. The result has been found to be very much satisfactory.